Examining the Effects of Green Financing on Sustainable Development in Iran - Tavakoli , Muhaddeseh; Momeni Vasalian, Hoshang; Ismail Nia Getabi, Ali Asghar; Seifipour , Roya (Management Strategies and Engineering Sciences, 2024)
Green financing is a crucial approach in executing all economic activities, and it is essential to formulate and adopt strategies, comprehensive environmental policies within the framework of laws and development policies, green job creation, and green financing. Given the significance and impact of green financing on the country's sustainable growth and development, this study analyzes the relationships between the green financing index and sustainable development using the Smooth Threshold Autoregressive (STAR) model. To achieve this, the green financing index is first calculated, followed by an analysis of the relationship between the green financing index and the country’s sustainable development. The results indicate that the threshold rate is 18%. Considering the differences in the coefficients obtained for the linear and nonlinear components of the model, the varying influence of sustainable growth on other variables is demonstrated. Furthermore, the findings reveal that before reaching the 18% threshold of sustainable development, the green financing index has a positive effect in the linear model. However, beyond this specified rate, its impact becomes negative and more substantial. The results of the diagnostic tests indicate that there is no serial autocorrelation or heteroskedasticity in the model, and the model has accurately captured all existing nonlinear behaviors, with the normality of the distribution being accepted.